Individual Factors Associated With Dietary Practices During Pregnancy - Dewi Susilawati; Nur Fadjri Nilakesuma (Universitas Islam Lamongan, 2021)
During pregnancy, nutrition is very important for the health of the mother and baby. Many impacts that occur if pregnant women experience nutritional deficiencies such as anemia, Protein Energy Deficiency, Low Birth Weight Babies and nutritional deficiencies can also affect the type of delivery. The incidence of anemia in pregnant women is 11.2%, pregnant women who experience KEK are 9.3%, while infants with low birth weight are 1.8%. One of the efforts to reduce nutritional deficiencies of pregnant women is to improve the quality of the mother's diet during pregnancy by practicing a good diet. Many factors influence the dietary practice of pregnant women, one of which is the socio-demographic of pregnant women. Objective: to determine individual factors (age, parity, education, pregnancy spacing) that are related to dietary practices during pregnancy. Methods: descriptive-analytical research type with cross-sectional design. The sample of this study was pregnant women who visited the Independent Practicing Midwife in Padang City in July - August 2021 as many as 100 pregnant women. Data processing by editing, coding, entry, tabulating, and cleaning. This study was analyzed by a chi-square test. Results: Individual factors related to dietary practice were age (P-Value 0.037), parity (P-Value 0.030), and education (P-value 0.017) while there was no relationship between pregnancy interval and dietary practice during pregnancy (P-value 0.661). Conclusions and Suggestions: there is a relationship between age, parity, and education with the dietary practices of pregnant women, therefore pregnant women should often consult and seek information related to good dietary practices during pregnancy so that nutritional deficiencies during pregnancy can be prevented.